Analysis of electrical conductivity of carbon nanotube-reinforced two-phase composites. (November 2022) - Li, Zaiwei; Li, Long-yuan
Abstract: This short paper presents a simple approach for calculating the effective electrical conductivity of carbon nanotubes-reinforced two-phase composite materials. The approach is developed by modifying the traditional effective medium approximation to include the effect of percolation threshold. The predicted electrical conductivity from the present approach is validated by using published experimental results. It is shown that the effective electrical conductivity of two-phase composites can be calculated by using the lower bound of the effective medium approximation if the inclusion volume fraction is below its percolation threshold, and the projection of the upper bound of the effective medium approximation if the inclusion volume fraction exceeds its percolation threshold. Graphical abstract: Image 1 Highlights: A simple model is proposed to characterize electrical conductivity of two-phase composites. Analytical formula is derived for calculating electrical conductivity of two-phase composites. The model is validated using experimental data obtained from different composites. The proposed model illustrates the effect of percolation threshold on electrical conductivity.